﻿Development of RP-HPLC methods for the analysis of Dexamethasone and Levofloxacin alone and in combinations used in the therapy of Covid-19 - Lily Peikova; Diana Tzankova; Miglena Smerikarova; Stefan Balkanski; Alexander Zlatkov (Pensoft Publishers, 2022)
In December 2019, the World Health Organization was informed of an outbreak of pneumonia of unknown etiology in Wuhan, Hubei Province, China. On January 7, 2020, a new type of coronavirus was isolated, with the WHO later officially calling it "COVID-19" and the International Committee on Taxonomy of Viruses naming the virus "SARS-CoV-2". On January 30, 2020, the WHO declared the severe acute respiratory syndrome coronavirus 2 outbreak a public health emergency of international concern, making it an unprecedented global public health challenge. From a scientific and literary reference, it was established that the main drugs in the therapy with Covid-19 are Dexamethasone and Levofluoxetine. For this reason, we pay attention to the analysis of these two medicinal products. In the literature, we did not find an analysis of a combination of Dexamethasone and Levofloxacin. Development and validation of a highperformance liquid chromatographic analytical procedure for simultaneously determining Dexamethasone and Levofloxacin in a synthetic mixture is described in this paper. The separation was made with a LiChrosorb RP 18 (250 × 4.6 mm) column, at 25 °C temperature,with isocratic mode andmobile phase,containingt acetonitrile and woter (70-30v/v). Eluent was monitored at 254 nm and the flow rate was 1.0 ml/min. Dexamethasone and Levofluoxetine were effectively separated with retention time (tr) of 4.69 min and 14.51 min,respectively,with in the selected chromatographic conditions.The method was validated for analytical parameters: specificity, linearity, precision, accuracy,andlimits of detection and quantitation. The calibration curves were linear inthe concentration range of 12.5 to 100.0 μg/ml for Dexamethasone and Levofloxacin, and the regression coefficientswere more than 0.999. For Dexamethasone and Levofloxacin the recovery was 100.01% and 100.04%, respectively. This analytical procedure is applicable for the quality control of drug formulations.